Late Jurassic theropod dinosaur bones from the Langenberg Quarry (Lower Saxony, Germany) provide evidence for several theropod lineages in the central European archipelago - Evers,Serjoscha W.; Wings,Oliver (PeerJ, 2020)
Marine limestones and marls in the Langenberg Quarry provide unique insights into a Late Jurassic island ecosystem in central Europe. The beds yield a varied assemblage of terrestrial vertebrates including extremely rare bones of theropod from theropod dinosaurs, which we describe here for the first time. All of the theropod bones belong to relatively small individuals but represent a wide taxonomic range. The material comprises an allosauroid small pedal ungual and pedal phalanx, a ceratosaurian anterior chevron, a left fibula of a megalosauroid, and a distal caudal vertebra of a tetanuran. Additionally, a small pedal phalanx III-1 and the proximal part of a small right fibula can be assigned to indeterminate theropods. The ontogenetic stages of the material are currently unknown, although the assignment of some of the bones to juvenile individuals is plausible. The finds confirm the presence of several taxa of theropod dinosaurs in the archipelago and add to our growing understanding of theropod diversity and evolution during the Late Jurassic of Europe.
Keywords: Theropoda; Dinosauria; Late Jurassic; Langenberg Quarry; Harz Mountains; Lower Saxony Basin